2023
DOI: 10.1590/1517-8692202329012023_0010
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Balance Training on Shooting Quality in Basketball Players

Abstract: Introduction: Inspired by the traditional way of basketball training, this paper presents a new method of balance training, which can effectively improve basketball players’ coordination ability and shooting skills. Objective: Explore whether balance training can improve the coordination ability and shooting ability of athletes. Methods: Twenty players from a professional basketball team were randomly selected as volunteers, and divided into two groups randomly. The control group adopted the traditional bask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“… Haghighi et al (2023) demonstrated that PT can lead to improvements in dribbling, passing, shooting skills, and other basketball-specific performance measures. Basketball shooting skills rely on physical fitness such as upper body and leg strength for generating shot power, and core stability for balance and control ( Candra et al, 2018 ; Aksović et al, 2020 ; Cabarkapa et al, 2022 ; Jing, 2023 ). Upper body strength, especially in the shoulders, arms, and chest, is essential for generating the necessary power to shoot the basketball, which is particularly important for long-range shots such as three-pointers ( Cabarkapa et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Haghighi et al (2023) demonstrated that PT can lead to improvements in dribbling, passing, shooting skills, and other basketball-specific performance measures. Basketball shooting skills rely on physical fitness such as upper body and leg strength for generating shot power, and core stability for balance and control ( Candra et al, 2018 ; Aksović et al, 2020 ; Cabarkapa et al, 2022 ; Jing, 2023 ). Upper body strength, especially in the shoulders, arms, and chest, is essential for generating the necessary power to shoot the basketball, which is particularly important for long-range shots such as three-pointers ( Cabarkapa et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Good balance provides a solid foundation for shooting. It allows players to set their feet properly, align their body towards the basket, and execute the shot with proper form ( Jing, 2023 ). The improvement of these physical fitness attributes in included studies could explain the effectiveness of PT on shooting skills.…”
Section: Discussionmentioning
confidence: 99%